Epistemological Analysis of Knowledge Management Implementation in Learning at IAIN Kediri - Yusuf, Moh. Asror; Arifin, Mohamad Zaenal (Didaktika Religia, 2022)
Knowledge is one of the important assets owned by universities. The core business of higher education is the development of knowledge, so of course, knowledge assets are very important to be developed by universities. Knowledge occupies an important position because it can stimulate innovations in the activities of the Tridharma of Higher Education. Knowledge management needs to be done so that the knowledge possessed by each individual in the organization can be managed properly. This study examines the implementation of knowledge management in the field of learning at IAIN Kediri, then conducts an epistemological analysis. The approach used is a qualitative approach. This research was conducted at the State Islamic Institute (IAIN) Kediri, Indonesia. The sources of data for this research are leaders, both at the rectorate, faculty, and unit levels, and lecturers. The data collection method is the method of documentation, questionnaires, and in-depth interviews and observations. The results of this study indicate that the management of learning at IAIN Kediri has applied the principles of knowledge management. The institution has made efforts to realize knowledge creation and knowledge sharing among lecturers in improving learning performance. Both of these things continue to be pursued although there are still some obstacles. However, there are still several obstacles and challenges that must be resolved in developing a culture of knowledge creation and knowledge sharing, developing facilities and human resources in the IT sector for the field of learning, and improving the online learning document storage system.